P09.35 Eradication of syphilis?—not there yet ongoing public health response to a syphilis outbreak in the northern territory, australia. (13th September 2015) - Garton, L; Gunathilake, M; Su, JY; Russell, M; Yip, TW; Hope, A; Ryder, N; Thalanany, M; Krause, V
Abstract : Introduction: An extensive outbreak of infectious syphilis in the Northern Territory (NT) was identified in Central Australia and Katherine regions in 2014. The NT Centre for Disease Control (CDC) launched an outbreak response to contain it. Methods: A multi-disciplinary outbreak response team was formed to drive the response. Comprehensive testing and treatment data were regularly collected and used to monitor the outbreak and to guide the response measures. Opportunistic testing was proactively promoted in affected regions. In areas with high numbers of cases and untraceable contacts, a community-wide screen using a point-of-care test (PoCT) for syphilis was conducted for those aged 12–30 years. Local guidelines were followed in treatment and contact tracing. Updates on the outbreak response were communicated to the affected communities regularly. Results: As of 7 April 2015, 112 cases (60 females and 52 males) of infectious syphilis were detected, consisting of 74 and 38 confirmed and probable cases, respectively. Their ages ranged from 12 to 37 years (median: 17; inter-quartile range: 15–20.5). Community-wide screening was conducted in 2 remote Aboriginal communities with combined population coverage of 62.7% and a prevalence of 8.4% in the targeted age group (12–30 years). All positive PoCT results were confirmed by normal syphilis serology tests. Conclusion: Effective syphilis outbreak control requires up-to-date surveillance on testing and treatment as well as an outbreak response team capable of adopting the best disease control measures in a timely fashion to the different stages and needs of the outbreak. In particular, using PoCT for community screening is proving to be an extremely useful case finding method, shortening the time to treatment and thus the period of infectiousness in communities most affected. Further control of the outbreak will require inter-jurisdictional collaboration. Disclosure of interest statement: There are no conflicts of interest